The Cost of an Upper Gastroduodenal Endoscopy: An Activity-Based Approach - Ralph Crott; Nicholaos Makris; Alan Barkun; Carlo Fallone (Canadian Journal of Gastroenterology)
The cost of medical procedures is often unknown, but is nevertheless crucial for setting reimbursement and health care policies. The cost of an upper gastroduodenal endoscopy was investigated in ambulatory adults in a large academic hospital in the province of Quebec, from the perspective of the hospital.